Relationship between emotional intelligence and empathy towards humans and animals. - Gómez-Leal, Raquel; Costa, Ana; Megías-Robles, Alberto; Fernández-Berrocal, Pablo; Faria, Luisa (Peer J., 2021)
Previous research has highlighted that Emotional Intelligence (EI) is related to an array of positive interpersonal behaviours, including greater human empathy. Nonetheless, although animals are an integral part of our lives, there is still a lack of clarity regarding the way in which EI relates to empathy towards animals. The aim of this study was to investigate the relationship between EI and empathy towards humans and animals. We used the Trait-Meta Mood Scale to assess EI, the Interpersonal Reactivity Index to assess empathy for humans, and the Animal Empathy Scale to assess empathy for animals. Our findings revealed a positive relationship between empathy for humans and animals. The results also supported the idea that EI is positively related to empathy for humans, while the relationship between EI and empathy for animals was dependent on whether or not the participants had experience with pets. In addition, multiple regression analysis showed that the variables that best predicted empathy for animals were having a pet (or not), age, gender and human empathic concern. Finally, the relationship between human empathic concern and empathy for animals was stronger in participants who had pets. These findings provide a better understanding of the mechanisms underlying empathic behaviour and suggest that empathy for humans and animals can be influenced by different factors. Limitations and future lines of research are discussed.
Keywords: Madurez afectiva; Empatía; Relaciones humanas; Relaciones hombre-animal; Emotional intelligence; Empathy; Empathy for animals; Empathy for humans